A review of the application of radiative sky cooling in buildings: Challenges and optimization. (1st August 2022) - Wu, Yifan; Zhao, Hengxin; Sun, Hongli; Duan, Mengfan; Lin, Borong; Wu, Shuangdui
Graphical abstract: Highlights: Developments, challenges, and improvements of radiative sky cooling in buildings are reviewed. The actual effects of radiative sky cooling on the indoor environment are emphasized. Five main challenges with the current application of radiative sky cooling in buildings are presented. Switchable building envelopes are reviewed and attempted to be optimally combined with radiative sky cooling. Abstract: Radiative sky cooling (RSC), acting as a passive cooling method, reduces the heat gain by dissipating the excessive heat via reflective and radiative approaches. The heat sink of RSC is mainly the deep space with temperatures close to absolute zero. Recent research shows that RSC offers high cooling potential in many fields because of its wide and low-temperature heat sink. Most studies on RSC focus on equipment performance and material development, and only a few addresses its actual applications in cooling buildings. Considering the potential of RSC in building energy saving, this paper reviews the developments, challenges, and improvements of RSC in buildings which is one of the main application scenarios for RSC. The paper reviews five main challenges with the current applications of RSC in buildings, based on the discussion of the cooling effect of RSC in the indoor built environment. The application of RSC in buildings is more related to its passive integration with the building envelope, which limits its overall effectiveness. Therefore, the combinations of RSC with active building cooling systems are further reviewed and analyzed in order to improve RSC dynamic performance. For future use, some advanced building envelopes, such as switchable building envelopes, are discussed, along with RSC. Using the optimal combination of the two, an optimal solution for the application of RSC in buildings is sought, providing a reference and basis for the application of RSC in buildings.